Monitoring of draft beer fermentation process by electronic nose - Phetchakul, Toempong; Sutthinet, Chalin (My University, 2014)
The draft beer fermentation process was monitored by using electronic nose. The system used the seven types of generally commercial metal oxide gas sensor in array. The selected process was one of the commercial processes and the data were gathered every hour for 10 day process which was 240 steps. It was processed for monitoring the chemical reaction for quality control. The results showed the good difference of the chemical reaction of the each day very clearly. The signature processing showed the variance 98.78%, 96.55% of the first component (PC1) and 2.3% of the second component (PC2), which was sufficiency for data explanation in 2D plot. It would be useful for production process to ensure a quality standard. © (2014) Trans Tech Publications, Switzerland.
Keywords: Draft beer; Electronic nose; Fermentation; Monitoring; PCA